The RNA-Recognition Motifs of TAR DNA-Binding Protein 43 May Play a Role in the Aberrant Self-Assembly of the Protein - Zacco, Elsa; Martin, Stephen R.; Thorogate, Richard; Pastore, Annalisa (Frontiers in Molecular Neuroscience, 2018)
The TAR DNA-binding protein 43 (TDP-43) is a nucleic acid-binding protein implicated in gene regulation and RNA processing and shuffling. It is a ribonuclear protein that carries out most of its functions by binding specific nucleic acid sequences with its two RNA-recognition motifs, RRM1 and RRM2. TDP-43 has been identified in toxic cytosolic inclusions in neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitin-positive inclusions (FTLD-U). The unstructured C-terminus has prion-like behavior and has been considered the driver of the aberrant self-assembly of TDP-43. In this work, we set out to test the hypothesis that the RNA-binding domains could also play a role in protein aggregation. This knowledge could be of important value for understanding TDP-43 aberrant, disease-leading behavior and, in the future, inform the design of small molecules that could prevent or slow down protein aggregation by exploiting the RNA-binding properties of the protein. We investigated the behavior of the two tandem RRM domains separately and linked together and studied their self-assembly properties and RNA-binding ability with a number of biophysical techniques. The picture that emerges from our study suggests that this region of the protein plays an important and so far unexplored role in the aggregation of this protein.